O HERETYKU MAHOMECIE – OPOWIEŚĆ O NARODZINACH ISLAMU W LATOPISIE HELLEŃSKIM I RZYMSKIM DRUGIEJ REDAKCJI - Brzozowska, Zofia A. (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2020)
A piece of writing On the Heretic Muhammad concerning the life of Muhammad, the origin of Islam and the first Arab conquests in the 7th century is included in the second redaction of the Hellenic and Roman Chronicle, a medieval Russian historiographical source containing an outline of universal history. The aforementioned text was edited and translated into Polish following the manuscript of РГБ, собр. Пискарева (228), № 162, from 1485.